A latent class analysis of resilience and its association with patient-reported symptoms in patients with esophageal cancer after esophagectomy - Li, Yanran; Zhang, Zonghao; Ma, Xuanxuan; Zhang, Xue; Li, Shuwen (Frontiers in Psychology, 2023)
Abstract Purpose: To identify the latent classes of resilience in patients with esophageal cancer after esophagectomy and develop a deeper understanding of the association between these classes and patient-reported symptoms. Background: China accounts for more than half of the global burden of esophageal cancer , and patients with esophageal cancer experience numerous symptoms that affect their quality of life and prognosis. Given that resilience is a key element that alleviates the progression of symptoms, it may represent a potential means of to enhancing cancer patients' physical and psychological well-being. Methods: The study was implemented in the thoracic surgery departments of three tertiary hospitals in eastern China. The participants were patients who were still hospitalized after esophagectomy. Data were gathered by self-report questionnaires, and a latent class analysis was utilized to identify different categories of resilience among the patients. Results: A total of 226 patients were recruited. The three classes of resilience identified included high strength and striving (53.5%), medium resilience but weak self-recovery (35.9%), and minimal tenacity and external support (10.6%). Patients with low income (OR = 12.540, P=0.004) were more likely to be in the minimal tenacity and external support class. Patients without comorbidities (OR = 2.413, P = 0.013) and aged 66-70 years (OR = 4.272, P＜0.001) were more likely to be in the high strength and striving class. The patient-reported symptoms and symptom-related interference of patients after esophagectomy varied considerably among the three categories of resilience. Conclusion: Accurate interventions should be devised and executed according to the features of each type of resilience in patients after esophagectomy to maximize intervention efficacy. These findings highlight the important role of precision nursing.